2012
DOI: 10.3233/jvr-2012-0584
|View full text |Cite
|
Sign up to set email alerts
|

Beyond yellow ribbons: Are employers prepared to hire, accommodate and retain returning veterans with disabilities?

Abstract: Are employers ready to hire, retain and accommodate veterans with disabilities (VWDs) returning from engagements in Iraq and Afghanistan? A survey of 1,083 human resource professionals examined employer readiness in three areas: knowledge, beliefs/willingness and actions/practices, with an emphasis on the signature disabilities of Post Traumatic Stress Disorder (PTSD) and Traumatic Brain Injury (TBI). Overall, employers surveyed did have willingness to employ VWDs and saw some benefits in doing so. Yet, they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…Studies focusing specifically on veteran populations consistently find that depression and anxiety are associated with unemployment, but find no association between Post-Traumatic Stress Disorder (PTSD) and unemployment (Hamilton et al, 2015;Horton et al, 2013;Zivin et al, 2016). Research with human resource professionals found that, whilst the majority reported being willing to employ veterans with PTSD and Traumatic Brain Injury (TBI), several reported believing that employing veterans with mental health problems would involve more costs, more manager time, and were unsure if veterans with PTSD or TBI were more likely than others to be violent in the work place (Rudstam, Strobel Gower, & Cook, 2012). Physical health problems are also likely to cause difficulties finding and maintaining employment.…”
Section: Veteran Health and Employmentmentioning
confidence: 99%
“…Studies focusing specifically on veteran populations consistently find that depression and anxiety are associated with unemployment, but find no association between Post-Traumatic Stress Disorder (PTSD) and unemployment (Hamilton et al, 2015;Horton et al, 2013;Zivin et al, 2016). Research with human resource professionals found that, whilst the majority reported being willing to employ veterans with PTSD and Traumatic Brain Injury (TBI), several reported believing that employing veterans with mental health problems would involve more costs, more manager time, and were unsure if veterans with PTSD or TBI were more likely than others to be violent in the work place (Rudstam, Strobel Gower, & Cook, 2012). Physical health problems are also likely to cause difficulties finding and maintaining employment.…”
Section: Veteran Health and Employmentmentioning
confidence: 99%
“…The increasing proportion of older people in the workforce heightens the likelihood of more workers with disabilities, as research shows that the incidence and prevalence of disability increases with age (He et al 2005;Houtenville et al 2009). In addition, many veterans returning to civilian employment have some level of service-connected disability, often in the form of non-apparent disabilities such as depression, post-traumatic stress disorder and traumatic brain injury (Ramchand et al 2008;Richardson et al 2011); and many employers are not prepared to address disclosure issues or successfully accommodate these conditions (Rudstam et al 2012).…”
Section: Disability In the Workplacementioning
confidence: 99%
“…A third reason we encourage people to disclose is that it improves organizational policies and social norms. Employers report significant knowledge gaps regarding the numbers and needs of people with invisible disabilities (Rudstam, Gower, & Cook, 2012). In addition, employers often report being largely unaware of accommodation resources (Rudstam et al, 2012).…”
Section: Disclosing Helps Organizationsmentioning
confidence: 99%
“…Employers report significant knowledge gaps regarding the numbers and needs of people with invisible disabilities (Rudstam, Gower, & Cook, ). In addition, employers often report being largely unaware of accommodation resources (Rudstam et al, ). Taken together, this indicates that what initially seems like an intention to avoid hiring individuals with invisible disabilities may actually be due to a lack of experience that employers have with employees who have invisible disabilities.…”
Section: Disclosing Helps Organizationsmentioning
confidence: 99%